Evaluating Logistics Performances of Agricultural Prunings for Energy Production: A Logistics Audit Analysis Approach - Techane Bosona; Girma Gebresenbet (Logistics, 2018)
The utilization of agricultural prunings as renewable energy sources requires effective and efficient logistics systems. The objective of this paper was to map out logistics activities along the agricultural pruning-to-energy (PtE) value chains. It describes the logistics performances based on the existing and potential pruning biomass supply chains focusing on prunings from fruit tree, vineyards, olive groove, and up-rooted tree branches. A logistics audit analysis approach has been used for detailed assessment of logistics performances. The analysis was based mainly on primary data gathered using a structured data survey format targeting the existing and potential PtE initiatives in Spain, Germany, Denmark, France, and Poland. The analysis considered the major stages of the chain, such as pruning, harvesting, processing (e.g., baling and chipping), storage, transport, and the linkage between the different stages. The paper identified the constraints along the logistics chain and recommended appropriate interventions to promote the marketing of agricultural pruning focusing on the supply of quality bales and chips for renewable energy production, and to increase the sustainability of renewable energy generation from PtE initiatives. The study has indicated that there are economic, social, and environmental benefits of PtE initiatives, as well as opportunities to increase the implementation and sustainability of the system.